A new synthesis device for preparing polymer monolithic columns with less defects. Issue 170 (23rd March 2016) - Zhang, Hong-Bo; Yu, Bing; Liu, Yang-Chun; Yuan, Hua; Gao, Ming-Yan; Cong, Hai-Lin; Yang, Shu-Jing
ABSTRACT: In the stainless steel-tube, there will be volume shrinkage during preparing a polymer monolith. Stationary phase can not be completely filled in the column, and the gap will appear. This will seriously affect the separation. In this paper, we use a new device to prepare polymer monolith. And it effectively solves the problem. The resulting monolith has good porous structure and separation performance.